EFFECTIVE USE OF ARTIFICIAL INTELLIGENCE IN ENGLISH LESSONS - Muxtarova Aziza Zoxidjonovna (PEDAGOGS, 2025)
Abstract: In our article, we consider the possibilities of effective use of artificial intelligence (AI) in the process of teaching English. We analyze modern AI tools, such as chatbots, virtual assistants, automatic grammar and pronunciation checking systems, as well as adaptive learning platforms. We pay special attention to the advantages of AI in personalizing learning, increasing student motivation and developing language skills. We presented examples of successful implementation of AI in the educational process and recommendations for teachers on its effective use.